Sodelovanje med zdravniki družinske medicine in specialisti na različnih ravneh - Kopčavar Guček, Nena (Zdravniški vestnik, 2003)
Background. Progress of medical science, development of new technologies and new medications, aging of population, limitedsources, increasinghealth-consciousness and demands of the population require new approaches to the organisation of health - care. Besides all activities which protect andpreserve health of an individual, health care integrates several other activities, including the care at various levels. All health care activities in Slovenia, at primary and also at secondary and tertiary level have increased significantly in the past decade. The characteristics of overload at various levels vary significantly and should be analysed separately. A critical view of the present state of art may render possibilities for better access, decreased working load and include the efforts for maintaining on even improving the quality of primary health care. Moreover, it is absolutely necessary as a solid foundation for cooperation with care providers at higher levels. New communication technologies offer newpossibilities for communication between doctors at various levels of healthcare. Health reforms, transformations of health care system, new clinical guidelines and recommendations facilitate more rational healthcare and its higher quality. Collecting data on patient satisfaction, or their perception of quality of health care, beside standardized predictors of quality and pear monitoring enable feedback information for the health providers, which is essential Conclusions. Increasing demand of the patients at all levels of health care is overloading the normal functioning and demandschange in the health care system. The central, "gate keeper" role of the family practitioner coordinates treatment on the same level and offers possibility of referring to secondary and tertiary level. (Abstract truncated at 2000 characters).
Keywords: Bolnik, zadovoljstvo; Družinska medicina; Family Practice; Health Services; Health Surveys; Interprofessional Relations; Kakovost zdravstvenega varstva; Organization And Administration; Patient Satisfaction; Poklicni odnosi; Posvetovanje in napotila; Quality Of Health Care; Referral And Consultation; sodelovanje; Specialistične stroke medicinske; Specialties, Medical; zdravniki; zdravstvena dokumentacija; Zdravstvene službe; Zdravstveni pregledi